Freedom of expression and the desecration of flags and religious books in Israeli law (Stato, Chiese e pluralismo confessionale, 2019)
SUMMARY: 1. Introduction - 2. Flag Protection. Legislation - 3. Flag Protection. Jurisprudence - 4. Foreign Flags - 5. Desecration of Religious Books - 6. Conclusions.ABSTRACT: Freedom of expression is axiomatic to liberal democracy. However, extremely divergent paradigms about when it must be curbed are manifest in the legal systems of different countries, especially concerning hate speech and speech offensive to religious or patriotic feelings. The United States is more protective of freedom of expression even at the cost of deliberately ignoring the need - especially in culturally diverse societies common in democratic countries nowadays - for dialogue rather than confrontation and for a pluralistic respect of the dignity and integrity of others and that which they cherish. In contrast, the European paradigm willingly sacrifices freedom of expression for the sake of protecting the sensibilities of the different segments of society. The theoretical question of the proper perimeters of such infringements upon freedom of expression aside, legislation prohibiting the desecration of national symbols on the one hand, and of religiously venerated objects on the other hand, can be seen as a measure of the emphasis ascribed in a jurisdiction to tolerance and pluralism as a justification for limiting democratic rights. This paper is a critical review of the legislation and case-law of flag burning statutes, and statutes outlawing the desecration of religious books, in Israel.
Keywords: Diritto ecclesiastico comparato e straniero